2014
DOI: 10.3390/ijms151018856
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Targeting of the PI3K/Akt/mTOR Pathway: Toxicity Reduction and Therapeutic Opportunities

Abstract: The PI3K/Akt/mTOR pathway plays an essential role in a wide range of biological functions, including metabolism, macromolecular synthesis, cell growth, proliferation and survival. Its versatility, however, makes it a conspicuous target of many pathogens; and the consequential deregulations of this pathway often lead to complications, such as tumorigenesis, type 2 diabetes and cardiovascular diseases. Molecular targeted therapy, aimed at modulating the deregulated pathway, holds great promise for controlling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 165 publications
(261 reference statements)
0
40
0
Order By: Relevance
“…It will be important to incorporate and utilize the experience from oncology in using PI3K/AKT/mTOR inhibitors to treat cancer when considering clinical trials that may use these drugs for targeted treatment of segmental overgrowth disorders [Li and Wang, ; Porta et al, ; Yu et al, ]. In 2014, there were more than 50 drugs inhibiting the PI3K/AKT/mTOR pathway in development, with 60% of them being used in clinical trials [Li and Wang, ]. Potential problems may include toxic side effects and drug resistance.…”
Section: Obstacles To Inhibitor Therapies Of the Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…It will be important to incorporate and utilize the experience from oncology in using PI3K/AKT/mTOR inhibitors to treat cancer when considering clinical trials that may use these drugs for targeted treatment of segmental overgrowth disorders [Li and Wang, ; Porta et al, ; Yu et al, ]. In 2014, there were more than 50 drugs inhibiting the PI3K/AKT/mTOR pathway in development, with 60% of them being used in clinical trials [Li and Wang, ]. Potential problems may include toxic side effects and drug resistance.…”
Section: Obstacles To Inhibitor Therapies Of the Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Our previous study also confirmed that the protective effect of Acanthopanax senticosus and pioglitazone on ischemia-reperfusion cardiomyocytes was related to the PI3K/Akt signaling pathway. However, studies on the PI3K/ Akt pathway has not achieved satisfactory results when applied in clinical trials (Li and Wang, 2014), and possible prevention measures based on the PI3K/Akt pathway mechanism have not yet been studied. Previous studies have found that toll-like receptor 4 (TLR4) is an upstream factor of the PI3K/Akt signaling pathway (Ha et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Data about elevated mTORC1-activation in numerous solid tumours and lymphomas are increasing. Our experimental and in vivo xenograft results suggest that the addition of rapalogues to treatment protocols could be beneficial not only in mantle cell lymphomas (MCLs) but also in other lymphomas with high mTORC1 activity -such as Hodgkin lymphomas, non-germinal center type diffuse large B-cell lymphomas and acute lymphoblastic leukemias [24,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 95%
“…(72 h treatment; co: control; TGF-b1: TGF; Rap: rapamycin; oka: okadaic acid; no inh: without PP2A inhibitor treatment; apoptosis was detected by flow cytometry.). other tumours by increasing or restoring sensitivity to currently available treatment modalities [32,[37][38][39] and to endogenous regulators such as TGF-b1. However, the complex in vivo effects of mTOR inhibition, the availability of endogenous negative regulators (including TGF-b1) and the net effect of these factors need to be clarified in further studies.…”
Section: Discussionmentioning
confidence: 99%